"Quem te indicou?" os ambientes sociais virtuais e o comportamento de consumo os homens - Costa, Williana de Souza (2015)
The virtual social environments, in particular their media, quickly became social areas on the Internet used quite often by its users, serving not only as major search channels of information but also online sites to interact with persons, contributing to the development of opinions about a certain issue under the influence of various external aspects contained in these spaces. This brings to the consumption a new way of figuring out how consumers take their final decisions. Thus, the main objective of this research was to analyze the extrinsic influences (also considered social) in the consumption held by men in the virtual social media. So it was traced a methodological way to accomplish the goal, setting this research to qualitative exploratory/descriptive procedure, developed in two concurrent stages: interviews and focus group online, conducted with male users of virtual social media. Such collection technique data were triangulated and analyzed using content analysis technique, aided by NVivo software. The results showed that, between the five categories of social influences studied (family, reference groups, social class, culture and subculture), the most influential on consumption are the reference groups, culture and subculture. By this analysis, it was drawn up a male consumer profile as active agent in the purchase decision process in virtual environments, mainly by their interactions in social media to which they belong. The findings show men as well-informed consumers, financial controllers, who do not see social media as buying spaces, but admit their persuasive power at the time of choice.